ANALISIS BISNIS SECARA SYARIAH PADA TRANSAKSI ELEKTRONIK DALAM KAJIAN FILSAFAT HUKUM ISLAM - Nur Aisyah Thalib; Thalib, Abd (UIR Law Review, 2019)
Trading transactions are not just done conventionally, where buyers and sellers meet in person. Now transaction has turned into a cyber-spaced transaction, where trading transaction is done through social networks, computers, mobile phones, and so on. Such a transaction is called an online trading transaction. (e-commerce). This article aims to analyze the study of the philosophy of Islamic law about business in the Shariah on electronic transactions. This writing uses normative methods of research that are descriptive. The source of legal material uses primary legal material such as regulations of legislation-invitations and secondary legal materials such as books and all scientific publications on related legal research. Data collection techniques using the study of libraries from both print and electronic media (internet). Based on the results of research and data analysis, to date Indonesia has not had a legal instrument to accommodate the development of e-commerce. While the law is one of the main ornaments in business. In the absence of special regulations governing virtual agreements, automatically such agreements on the Internet will be governed by applicable non-electronic agreement laws.